Meningkatkan Pengelolaan Keuangan Dana Haji di Reksadana Perspektif Hukum Ekonomi Syariah - Rizki Amalia Marfelina (CV. Creative Tugu Pena, 2024)
The BPKH (Hajj Fund Management Agency) institution, based on the legal regulation of Law No. 34/2014, explains that the organization handling the financial funding of Hajj funds aims to develop and improve the quality and efficiency in implementing the Hajj pilgrimage. It also aims to optimize the use of investment costs for public interests, specifically focusing on legal protection in optimizing the management of Hajj funds in mutual funds as an institution that collects funds from the community to implement the Hajj pilgrimage. The BPKH must adhere to and comply with applicable regulations that uphold honesty, transparency, and accountability. Therefore, the investment of Hajj financial funding is focused on securities, gold, and mutual funds. Priority is given to systems that implement effective investments to ensure optimal performance and generate profits to prevent an increase in financing each year. This type of research is a juridical-normative legal study with an analysis related to issues regarding optimizing Hajj fund placements by BPKH and legal protection for Hajj pilgrims. The results of this research explained through descriptive qualitative analysis, conclude that Hajj pilgrims must receive full protection and should be entitled to their rightful rights, particularly in Hajj financial funding.